Провінційний код драматургії Григорія Квітки-Основ’яненка - Яблонська, Ольга Василівна (Східноєвропейський національний університет імені Лесі Українки, 2013)
Політологічний та ідеологічний аспекти дослідження забезпечили вирізнення у драматургії Григо-рія Квітки-Основ’яненка таких опозиційних пар, як «столиця імперії – рідна земля», «варварська Росія – циві-лізована Європа», наївність / хитрість місцевого населення, «своє чуттєве (морально-етичне) – чуже раціональне».Political and ideological aspects of the study provided the decryption code provincial drama of Grigoriy Kvitka-Osnovyanenko. It is traced patterns such as inferiority complex, pettiness, Little Russian expression, intellectual and spiritual corrosion, corruption, deception and rhetoric of self-congratulation, oppositional pairs «capital of empire  the native land», «barbaric Russia  civilized Europe», naive / trick of the local population, «his sense (moral and ethical)  alien rational». In the textes «Coming from the capital, or the turmoil in the provincial town», «Noble elections», «Noble elections, part two, or a police officer selection», «Shelmenko  district clerk» is showed provincial mechanisms (without) orders. Plots of works «Clairvoyant» and «Voyagers» contain evidence of military policy of the Russian Empire. Decoupling of such dramas as «Courtship in Goncharovka», «Shelmenko-Denschyk», «Boy-zinkan» is provided by image of experienced and cunning Moskal.
Keywords: драматургія Григорія Квітки-Основ'яненка; провінційність; просвітительські акценти; комплекс меншовартості; міщанство; риторика обману та самовихваляння